Studi Kelayakan Perlindungan Pesisir Berkelanjutan melalui Integrasi Pemecah Gelombang Bambu dan Budidaya Kerang Hijau - Izqi Yustina Ammylia Yusuf; Ahmad Didin Khoiruddin; Nita Yuanita; Alamsyah Kurniawan (Jurnal Teknik Sipil, 2023)
Abstract One pressing issue posing a significant threat to the coastal ecosystem is abrasion. Therefore, it is imperative to implement an effective and stable coastal protection structure using readily available and cost-effective materials combined with green mussel cultivation to bolster economic benefits for the community. The methodology employed in this study encompasses the integration and analysis of secondary data and the collection of archival information. The findings indicate that the ecological conditions of the waters in Bedono Village, Sayung District at Demak Regency meet the necessary criteria for green mussel cultivation. Bamboo with a minimum length of 7.5 meters and a planting depth of 2 meters is utilized. Financially, this approach proves to be quite advantageous, yielding a Net Present Value (NPV) of Rp1,202,383 for the stake method of green mussel cultivation. The Net Benefit-Cost Ratio (Net B/C) for the stake method of green mussel cultivation is 1.20. Based on the NPV and Net B/C feasibility criteria, the stake method of green mussel cultivation is considered viable. This structural concept is evaluated as adhering to ecological principles across all its components. Keywords: Abrasion, breakwater, green mussel, natural coastal protection